Approaching ICC in the EFL classroom : a state of the art. (2023)
The present state of the art has the purpose of analyzing documentation that reports the status of the intercultural communicative competence implementation and investigation in the EFL classroom. This research follows a qualitative paradigm framework, and its type is documentary research. Data was reviewed and compiled using two detailed rubrics systematically. The documents’ corpus contained information for the last ten years in Colombian universities. Findings show that ICC implementation has been used to foster critical thinking, cultural awareness, and tolerance when integrated into the classroom through several pedagogic strategies and methodologies demonstrating positive results.